Exposure to high-temperature and high-humidity environments associated with cardiovascular mortality - Yalan Wu; Xiangrong Feng; Jinmei Li; Mengjun Li; Yao Wang; Weihui Lu; Huanhuan Luo (Ecotoxicology and Environmental Safety)
Aging populations are susceptible to climate change due to physiological factors and comorbidities. Most relevant studies reported the effect of temperature on cardiovascular disease (CVD)-related mortality in aging populations. However, the combined effects of temperature and humidity on CVD-related mortality remain unclear. Here we used the Global Burden of Disease (GBD) database to analyze CVD burden and its impact on the incidence of CVD in individuals exposed to high-temperature and high-humidity (HTH) environments. The prospective China Health and Retirement Longitudinal Study (CHARLS) cohort was used to further analyze the relationship between exposure to HTH environments and CVD mortality in middle-aged and elderly individuals. We found significant positive correlations between the estimated annual percentage change of CVD and age-standardized rate, wet bulb globe temperature, and Humidex worldwide. In the CHARLS, a higher CVD mortality rate was significantly associated with exposure to HTH environments (P < 0.01). Long-term HTH environment exposure increased the risk of an abnormal low-density lipoprotein cholesterol (LDL-C) level (hazard ratio [HR], 1.30–2.44) and abnormal total cholesterol (TC) level (HR, 1.21–2.13), but the impact on high-density lipoprotein cholesterol (HDL-C) level was unclear. The mortality risks of long-term exposure to HTH environments were increased for middle-aged and elderly individuals with abnormal LDL-C (HR = 0.84–3.57) and TC (HR = 0.78–2.41) levels. These findings suggest that exacerbated dyslipidemia caused by long-term HTH environment exposure may be a key risk factor for CVD-related mortality in middle-aged and elderly individuals and suggest research directions into the effects of HTH environments on human health.